A Phase 1 Study of Intravenous Busulfan as a Conditioning Regimen for Multiple Myeloma. Issue 12 (December 2019) - Radhakrishnan, Sabarinath V.; Boyer, Michael; Sherwin, Catherine M.; Zangari, Maurizio; Tricot, Guido
The efficacy of melphalan (MEL) 140 mg/m 2 pre-transplant conditioning versus MEL 200 mg/m 2 for the elderly is still debated. We hypothesized that single-agent intravenous busulfan (BU) would show significant anti-myeloma efficacy and be better tolerated by elderly patients. A prospective 3+3 dose escalation study enrolled symptomatic multiple myeloma (MM) patients 65 years or older with SWOG performance 0–2 for treatment with intravenous BU pre-transplant at different administration levels. The primary objective was to determine the maximum tolerated dose (MTD) of BU that could be safely given over the least number of days. All patients, except one, received maintenance treatment post-transplant, mostly for 2 years. We enrolled 13 patients, mean age of 73 years (range 68–80). Pharmacokinetic analysis showed no greater than 2% accumulation in the 13 patients, confirming a lack of accumulation in the multi-dose regimen. No deaths occurred in the peri-transplant period. Grade 3/4 adverse effects were hematological, no dose-limiting toxicity was observed and MTD was not reached. Three patients developed grade 3 mucositis but none developed veno-occlusive disease. Ten (77%) patients achieved a complete remission (CR) post-transplant with a remarkably long average time to best response of 6.7 months (range: 6–14 m), and two attained a partial response. Median overall survival was 84 months (95% CI, 21–104) and the median progression-free survival was 60 months (95% CI, 9–93). Our results suggest that IV BU could be an alternative conditioning regimen to MEL 140 in elderly patients with MM, and supports future randomized trials.